Bibliometric assessment of scholarly publications on wāqf (Islamic Endowment) - Yusuf, Aliyu Olugbenga; Junurham, Nur Leyni Nilam Putri; Adam, Usman Ahmed (IIUM Press, 2021)
This study aims at exploring and evaluating the growth and distribution of scholarly publications relating to wāqf using the evolving Bibliometrics technique for the period 1914-2019. For the established period (1914-2019), a total of the 476 scholarly papers were extracted using Scopus database. Basic inclusion and exclusion criteria were applied to ensure the theme of the study is critically analyzed. This study analyzes the documents based on various bibliometric measures such as year wise growth of publication, most productive wāqf authors, productive countries in wāqf publications, most productive wāqf journals, leading sponsors organization on wāqf, identification of important authors’ key words in wāqf publications, and characteristics of highly cited wāqf publications. The adopted bibliometric analysis helps determine special trends in wāqf and provides a basis for more wāqf multidisciplinary collaboration and research. Among the findings: Journal of the Economic and Social History of the Orient is the journal with the highest number of wāqf scholarly publications within the designated period; Timur Kuran is the author with the highest number of publications on wāqf while 2018 and 2017 recorded the most number of publications on wāqf. Wāqf authors from Asian countries such as Malaysia, Indonesia and Turkey have high level sponsor support. This study only explored Scopus online database to harvest scholarly publication on Wāqf.